American Iron, 1607-1900 - Gordon, Robert B. (Robert Boyd), 1929- (Book collections on Project MUSE., 2019)
By applying their abundant natural resources to ironmaking early in the eighteenth century, Americans soon made themselves felt in world markets. After the Revolution, ironmakers supplied the materials necessary to the building of American industry, pushing the fuel efficiency and productivity of their furnaces far ahead of their European rivals.